Leader Member Exchange dalam Membangun Komunikasi Efektif di Pondok Pesantren - Zamroni, Zamroni; Baharun, Hasan; Hefniy, Hefniy; Bali, Muhammad Mushfi El Iq; Hasanah, Kusmiyatun (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study aims to analyze and understand the leader-member exchange in building effective communication at Nurul Jadid Islamic Boarding School, Paiton, Probolinggo, by focusing its study on the Fathimatuzzahro area '. This study uses a qualitative approach to the type of phenomenology, in which the researcher tries to understand the phenomena that occur in the institution, through interviews, observation, and documentation. The results of his research show that the leader-member exchange in creating effective communication in the Fahtimatuzzahro area 'is carried out through three strategies, namely; Affect, where communication between leaders and subordinates shows more intimacy, does not look at social status but is consistent in carrying out their duties and responsibilities. Contribution, where each individual, both the leader and the leader, is expected to be able to contribute to the achievement of mutually determined goals. Professional Respect, as a form of respect and mutual respect for what has been done by each individual, both leaders, administrators, and students